Modifying M‐44s to reduce risk of activation by swift fox - Julie K. Young (Wildlife Society Bulletin)
ABSTRACT M‐44s are spring‐powered sodium cyanide ejectors commonly used in the United States to manage livestock depredation by coyotes (Canis latrans). While highly selective for canids, improvements could reduce risk to nontarget canids, especially State‐Endangered or ‐Threatened canids such as the swift fox (Vulpes velox). In 2012–2013, we tested M‐44s set at modified heights to determine whether height modifications reduced risk to swift foxes without reducing activation rates by coyotes. We presented captive coyotes housed at the USDA National Wildlife Research Center's Predator Research Facility, Millville, Utah, USA, with M‐44s at various test heights to determine a height that would still ensure activation and then M‐44s set at 15‐cm height were placed in pens with captive swift foxes at the Cochrane Ecological Institute, near Cochrane, Alberta, Canada, to evaluate their ability to activate M‐44s. M‐44s were next set in the field as 31 matched pairs within North Dakota, USA. For each matched pair, 1 was set at standard height, where the body of the device was entirely below ground level and only the mouth piece was above ground, and 1 at a modified height, where the top of the mouth pieces was set 15–18 cm above ground level. Camera traps were used to monitor wildlife activity at M‐44s. Despite equivalent visitation rates based on camera‐trap data, only one modified M‐44 was activated by a coyote, whereas 19 M‐44s set at standard height were activated by coyotes. No swift foxes were observed during field trials, but red foxes (V. vulpes) were observed at 2 sets and did not activate the M‐44s. Modifying the height of M‐44s appears to reduce activation risk for nontarget canids, but also reduces the rate of activation by coyotes. Thus, height modifications to M‐44s may not be practical or efficient in areas with little or no risk to nontarget canids because of compromised coyote activation rates, but should be considered as an option to enable use of M‐44s for coyote management in areas where M‐44s are not currently used because nontarget, small canids may co‐occur. Published 2016. This article is a U.S. Government work and is in the public domain in the USA.